Karakteristik Batuan Karbonat Paleozoikum Formasi Silungkang, Cekungan Ombilin, Sumatera Barat, Indonesia - Ugi Kurnia Gusti (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The Silungkang Formation, part of the Peusangan Group in the Ombilin Basin of West Sumatra, Indonesia, has long been classified as a siliciclastic unit. However, recent fieldwork and petrographic analysis from limestone outcrops near Taratak Banca Village suggest there may have been carbonate development in the area during the Paleozoic. Observations in the field show a greyish white, weathered limestone with a crystalline texture. Although there were no visible fossils were found, the carbonate rock shows signs of tropical weathering and surface dissolution. Thin section analysis reveals that the limestone is made up almost entirely of calcite (around 98%), with a small amount of opaque minerals. The calcite grains, which range from 0.3 to 1.5 mm, display strong birefringence, moderate relief, and sutured grain boundaries—signs of extensive recrystallization. Other geological features like calcite-filled microfractures and quartz veins show an influence of tectonic activity, likely related to regional orogeny processes. The absence of fossils and the highly crystallize calcite mineral suggest it has undergone considerable diagenetic alteration, that could possibly related depositional environment of a deeper marine setting followed by post-depositional changes. Despite the lack of fossil evidence, the carbonate characteristics interpreted deposited at a mid- to outer-ramp carbonate setting that was later deformed and recrystallized. These findings highlight the potential for previously unrecognized Paleozoic carbonate systems in Southeast Asia and open new possibilities for understanding the Silungkang Formation. Ongoing research could help refine its place in regional paleogeographic models and provide insight into the evolution of early Paleozoic carbonate platforms in western Indonesia.